Locating and tracking sound sources on a horizontal axis wind turbine using a compact microphone array based on beamforming. (March 2019) - Zhang, Cui Qing; Gao, Zhi Ying; Chen, Yong Yan; Dai, Yuan Jun; Wang, Jian Wen; Zhang, Li Ru; Ma, Jian Long
Highlights: An novel Beamforming Algorithm for identifying and tracking rotating sound sources is designed. The rotating sound identification and tracking accuracies of the algorithm are verified using a rotating simulation bench. Horizontal axis wind turbine is precisely tracked and identified according to the given step size in real time. Abstract: As the number and capacity of wind-power installations increases rapidly worldwide, the noise problems generated by wind turbines, which are increasingly being installed near residential areas, become increasingly prominent. Wind turbines can be approached as aerodynamic noise generation mechanisms for noise reduction purposes, for which a precisely localized sound source is key. Sound source recognition algorithms capable of locating the radial sound source position and relative azimuth angle of a rotating wind turbine blade in real time are rare. This paper proposes an algorithm based on classical beamforming theory with instantaneous speed and delayed azimuth angle rotation correction. First, the sound identification and tracking accuracies of the algorithm are verified using a rotating simulation bench; next, a small horizontal axis wind turbine is tracked and identified according to the given step size in the wind tunnel. The results show that the algorithm can precisely tracked and identified sound source of horizontal axis wind turbine in real time. Some errors were identified between the difference in two consecutive azimuth angles and a set step size of 60°, caused by fluctuations in rotating speed and characteristic vibrations of the wind turbine.